Paving the way to modernity: Prussian roads and grain market integration in Westphalia, 1821-1855 - Martin Uebele; Daniel Gallardo-Albarrán (European Historical Economics Society (EHES), 2014)
This study investigates the relation of pre-railroad transport infrastructure on Westphalian grain market integration in the early 19th century. It is motivated by recently found indications of macroeconomic change in Prussia such as increased demand for labour, disappearance of positive Malthusian shocks, and grain market integration. These coincide and correspond well with a number of institutional breaks such as border changes and state creation after the end of the Napoleonic Wars, liberal political reforms such as the abandoning of corporatist regulations in Prussia, and substantial public investment in paved roads in a number of Prussian provinces. In this article we show that (a) paved road connections mattered economically and statistically for bilateral rye and wheat price differences, (b) the usual dummy-variable approach to measure the effect of transport infrastructures proves to be unreliable and we propose a new indicator that takes into account the effects of the transport network (c) the role of the early railroad connections is not robust. In this pilot study we for the first time establish the correlation between economic development and pre-railroad transport infrastructure for a Prussian province, and thus call for more research on the causes of macroeconomic change in early 19th century Prussia.
Keywords: F1; N10; N73; 330; Transport infrastructure; grain markets; Prussia; 19th century